The expression profile of lung long non-coding RNAs and mRNAs in a mouse model of smoke inhalation injury. Issue 3 (1st March 2022) - Jiang, Zheng-Ying; Liu, Ming-Zhuo; Fu, Zhong-Hua; Liao, Xin-Cheng; Xu, Bin; Shi, Liang-Liang; Li, Jia-Qi; Guo, Guang-Hua
ABSTRACT: To study the potential expression of lung long non-coding RNAs (lncRNAs) and mRNAs during smoke inhalation injury (SII), using a SII mouse model that we created in our previous work. Microarray was used to investigate the lncRNAs and mRNAs profiles. A bioinformatics analysis was performed. Changes in the top 10 down-regulated and 10 up-regulated lncRNAs were validated using Quantitative Reverse Transcription-PCR (RT-qPCR). The acute lung injury (ALI) mouse model was successfully induced by smoke inhalation, as confirmed by the aberrantly modified cell numbers of red blood cells and neutrophils counts, increased levels of TNF-α, IL-1β, Bax, caspase-7, caspase-3, and decreased Bcl-2 content in lung tissues. When compared to the control mice, 577 lncRNAs and 517 mRNAs were found to be aberrantly expressed in the SII mice. According to the Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, the altered mRNAs were enriched in acute-phase response, oxidoreductase activity, oxidation-reduction process, glutathione metabolism, the wnt signaling pathway, and ferroptosis. A lncRNA-related competitive endogenous RNA (ceRNA) network, including 383 lncRNAs, 318 MicroRNAs (miRNAs), and 421 mRNAs specific to SII, was established. The changes in NONMMUT026843.2, NONMMUT065071.2, ENSMUST00000235858.1, NONMMUT131395.1, NONMMUT122516.1, NONMMUT057916.2, and NONMMUT013388.2 in the lung matched the microarray results. Our findings help to provide a more comprehensive understanding of the pathogenesis of SII as well as new insights into potential therapeutic targets. GRAPHICAL ABSTRACT: uf0001